Re-thinking "The Way We Think" – Metaphor, Metonymy & Blending in Usage-based Linguistics (KULT_online, 2011)
Conceptual Metaphor Theory and Conceptual Integration Theory, two highly influential cognitive semantic theories of meaning making, have over the past years come under considerable attack from usage-based and functional branches of linguistics. This varied volume sets out to explore the expository potential of both theories within a usage-based framework and, in most contributions, offers empirically solid applications as well as suggestions for theoretical reconfigurations.